Inkjet-printed polymer-based electrochromic and electrofluorochromic dual-mode displays - Pietsch, Manuel; Rödlmeier, Tobias; Schlißke, Stefan; Zimmermann, Johannes; Romero-Nieto, Carlos; Hernandez-Sosa, Gerardo (Journal of materials chemistry. C, Materials for optical and electronic devices, 2019)
We report on inkjet-printed dual-mode devices based on the synchronous electrochromic and electrofluorochromic effect of the polyindenofluoren-8-tryarylamine polymer (PIF8-TAA). Reference devices show switching times under 4 s, a coloration efficiency of 542 ± 10 cm2 C−1 at 395 nm, an electrochromic contrast of 50 ± 4% in the visible spectra and a fluorescence contrast ratio of 4.1 ± 0.3. The material is highly transparent in its neutral state and changes to a deep red color by oxidation. Utilizing PEDOT:PSS as electrode material, inkjet printing enabled the fabrication of freely, digitally designed device layouts providing a cost-efficient method for low-level display applications. The results highlight the applicability of digitally printed dual-mode EFCD for signage or advertisements.
Published online 17 May 2019
Gesehen am 31.10.2019